HUBUNGAN PERILAKU IBU DENGAN KARIES GIGI MOLAR PERTAMA PERMANEN PADA ANAK KELAS II-IV SDN LAMJAMPOK KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR - Mufizarni Mufizarni; Eka Sari Rahayu (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
Dental health is a part of body health that cannot be separated from one another. The results of the initial data examination of 10 students found that 9 students had untreated permanent first molar caries, 1 student did not have permanent first molar caries. The results of interviews with 9 out of 10 mothers, they did not know about the knowledge, attitudes and actions in maintaining the health of the permanent first molars. This study aims to determine the knowledge, attitudes and actions of mothers on caries of permanent first molars in grade II-IV students at SDN Lamjampok Ingin Jaya, Aceh Besar District. The research is analytic with a cross sectional study approach, the research sample is 77 students and 77 students' mothers. Data collection was obtained through direct examination of caries in the first permanent molars in students and interviewing students' mothers using a questionnaire. Data analysis used the chi-square test with a degree of confidence =0.05. The results showed that the P value of knowledge = 0.000, the P value of attitude = 0.000, and the P value of action = 0.002, meaning that there was a relationship between knowledge, attitudes and actions of the mother on permanent first molar caries. It can be concluded that there is a relationship between knowledge, attitudes and also actions on caries of permanent first molars in grade II-IV children at SDN Lamjampok. It is recommended for mothers to be able to increase knowledge, attitudes and also actions in the maintenance of teeth and mouth in children by seeking information through mass media and electronic media, so that children avoid permanent first molar caries.